Capital Markets Union from the perspective of the banking industry and prudential supervision. (3rd July 2015) - Alexander, Kern
Abstract : This article analyses some of the issues related to the financial stability risks associated with the European Commission's Green Paper on Capital Markets Union (CMU). The CMU proposal offers the potential for a more balanced and efficient provision of credit in EU capital markets through non-bank financial intermediaries that should enhance economic growth in Europe. Nonetheless, it introduces certain macroprudential regulatory risks that raise serious challenges for how EU policymakers plan to regulate the wholesale capital markets and particularly the shadow banking sector, which if not adequately addressed could substantially limit the effectiveness of the CMU project. The article suggests that the Commission has further work to do to ensure that the CMU addresses the macroprudential financial risks posed by bank disintermediation and the related systemic risks in the wholesale capital markets.